Influence of biodiesel and diesel fuel blends on the injection rate under cold conditions. (15th March 2015) - Tinprabath, P.; Hespel, C.; Chanchaona, S.; Foucher, F.
Highlights: The properties of biodiesel and biodiesel blends were tested in cold conditions. A kinematic viscosity correlation of fuel for cold conditions was developed. The influence of the percentage of biodiesel blend and temperature decreases on injection rate behavior was investigated. The discharge coefficients of biodiesel and biodiesel blends in cold conditions were investigated. Abstract: During start-up of the engine under cold temperatures, conditions can be different when biodiesel is used due to the low fuel injection pressure and the high cloud point and high pour point. It is consequently of interest to understand the behavior of the injector under cold conditions when operating with biodiesel and the impact on the combustion process. This article presents an experimental study of the influence of diesel fuel and biodiesel blends on injection flow. A Bosch CRI 3.1 piezoelectric injector was used on a typical diesel engine. Five fuel types were tested: diesel fuel, winter diesel fuel, two diesel–biodiesel blends (B20, B50), and pure biodiesel (B100). Injection pressures were set at 30–60 MPa for the study of the injection flow characteristics at room temperature, in non-vaporizing conditions and in cold conditions. The experimental results show that cold temperatures (−5 and −8 °C) have no effect on the injection delay for any of the fuels. The discharge coefficients for all fuels are lower than at room temperature. When the fraction of biodiesel in the blend is increased, the change in the discharge coefficients is insignificant. New correlation coefficients for estimating the kinematic viscosity and the discharge coefficient has been presented for cold conditions.